Environmental sustainability in Asian countries: Understanding the criticality of economic growth, industrialization, tourism import, and energy use - Ekwueme, Daberechi Chikezie; Lasisi, Taiwo Temitope; Eluwole, Kayode Kolawole (Sage Publications Ltd, 2023)
This paper examines the causation between economic growth, tourism import, industrialization, renewable energy, non-renewable energy use, trade openness, and environmental sustainability which is proxied by carbon emissions for 8 Asian countries (China, Japan, India, Indonesia, South Korea, Philippines, Thailand, and Vietnam) over 20 years. Causal relations were tested using Pooled Mean Group Autoregressive distributive lag model (PMG-ARDL) and Dumitrescu and Hurlin's (2012) panel granger causality test The PMG-ARDL model results reveal that in the long-run renewable energy usage, economic growth, and trade have a significant negative influence on the emission of carbon, while non-renewable energy usage, tourism import, and industrialization exhibit a significant positive impact on CO2 emissions of the sampled Asian countries. In the short run, renewable energy has a significant negative influence on CO2 emissions. While economic growth exhibit a significant positive influence on carbon emissions in the short-run. Furthermore, the Granger causality analysis reveals that there is a feedback mechanism between industrialization, tourism import, non-renewable energy, renewable energy, and CO2 emissions meaning that the future dynamics of carbon emissions in the sampled countries can be significantly explained by industrialization, tourism import, renewable energy, and non-renewable energy. Contrarily, trade and economic growth are good to explain the dynamics of carbon effusion of the sampled Asian countries in the future but without feedback. It is recommended that policymakers in Asian countries should formulate stringent environmental policies that will encourage industries in these countries to utilize clean energy sources so that economic growth will be achieved simultaneously with carbon neutrality.
Keywords: environmental sustainability; Carbon emissions; industrialization; trade openness; Asian countries; renewable and non-renewable energy; tourism import